What matters most to patients with multiple myeloma? A Pan-European patient preference study - Janssens, Rosanne; Lang, Tamika; Vallejo, Ana; Galinsky, Jayne; Morgan, Kate; Plate, Ananda; De Ronne, Chris; Verschueren, Margaux; Schoefs, Elise; Vanhellemont, Anneleen; Delforge, Michel; Schjesvold, Fredrik; et al. (Frontiers in Oncology, 2022)
Introduction: Given the rapid increase in novel treatments for patients with multiple myeloma (MM), this patient preference study aimed to establish which treatment attributes matter most to MM patients and evaluate discrete choice experiment (DCE) and swing weighting (SW) as two elicitation methods for quantifying patients’ preferences. Methods: A survey incorporating DCE and SW was disseminated among European MM patients. The survey included attributes and levels informed by a previous qualitative study with 24 MM patients. Latent class and mixed logit models were used to estimate the DCE attribute weights and descriptive analyses were performed to derive SW weights. MM patients and patient organizations provided extensive feedback during survey development. Results: 393 MM patients across 21 countries completed the survey (Myears since diagnosis=6; Mprevious therapies=3). Significant differences (p<.01) between participants’ attribute weights were revealed depending on participants’ prior therapy experience, and their experience with side-effects and symptoms. Multivariate analyses showed that participants across the three MM patient classes identified via the latent class model differed regarding their past number of therapies (F=4.772, p=.009). Patients with the most treatments (class 1) and those with the least treatments (class 3) attached more value to life expectancy versus quality of life-related attributes such as pain, mobility and thinking problems. Conversely, patients with intermediary treatment experience (class 2) attached more value to quality of life-related attributes versus life expectancy. Participants highlighted the difficulty of trading-off between life expectancy and quality of life and between physical and mental health. Participants expressed a need for greater psychological support to cope with their symptoms, treatment side-effects, and uncertainties. With respect to patients’ preferences for the DCE or SW questions, 42% had no preference, 32% preferred DCE, and 25% preferred SW. Conclusions: Quality of life, including physical, mental, and psychological health, was considered very important to MM patients. This underscores a need for including quality of life-related attributes such as pain, mobility and thinking problems in decision-making by healthcare stakeholders involved in MM drug development, evidence generation, evaluation, and clinical practice. This study highlights DCE as the preferred methodology for understanding relative attribute weights from a patient’s perspective.